Velocity measurements in the vicinity of the exit and inlet of a spiral bevel gear shroud - Simmons, Kathy; Johnson, Graham (2015)
In many aeroengines the accessory power offtake is achieved using a spiral bevel gear set running off one of the main shafts. The crown and bevel gears are housed in an internal gearbox. Over the past few years the Nottingham University Technology Centre (UTC) in Gas Turbine Transmission Systems has researched flow near spiral bevel gears both computationally and experimentally using a purpose-built test rig. In the current investigation the rig was configured with a Trent crown gear and slightly modified shroud covering the full 360° of the gear. No external containment chamber was fitted and all testing was conducted single-phase (air only) at 5,000 rpm. Laser Doppler Anemometry (LDA) was used to obtain the three components of flow velocity at a shroud exit slot and at shroud inlet. A 2D system was utilised and thus two measurements were required at each point to give the 3 velocity components.